FRAGMENTASI IDENTITAS DALAM NOVEL THE COLOR PURPLE KARYA ALICE WALKER - , JUSTINE NIKEN AFDA, S.S; , Dr. Wening Udasmoro, M.Hum., DEA., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research was motivated by the phenomenon of African-American identities that are fragmented. The issue of identity can be initiated by differences in class or social status. The growing influence making their identities also moved backward and forward and become unclear. The effect here is the imbalance of rights acquired by the inferior, in this case African-Americans, as citizens. Social situation that was created at that time to make this descent impaired in their lives. Their lives are filled with discrimination, slavery, oppression and injustice even among groups caused by the problem of racism. In this case they are of different races the black race. The subject was analyzed using a theory that reveals the identity of Thomas Fuch who began his term fragmented identity. Someone will be fragmented identity based on those experiences against their will. Fragmented identities were not consistent and they will have difficulty remembering certain events. The results of these research found some form of fragmentation of identity that exist in the African-American, due to the formation and isolation of the social system. Then the implications of fragmented identities can be seen as discrimination are covered, limited education, instability and shifting sexual identity, and dissociation.